COVID-19 Breakthrough Infection Among Vaccinated Population in the United Arab Emirates - Nihar Ranjan Dash; Hiba Jawdat Barqawi; Anas A. Obaideen; Hanae Qousae Al Chame; Kamel A. Samara; Rama Qadri; Salma Eldesouki (Springer, 2023)
Abstract Background Despite significant efforts to contain the Coronavirus Disease 2019 (COVID-19) pandemic through mass vaccination, numerous nations throughout the world have recorded breakout infections. The incidence and severity of COVID-19 breakthrough infections in the United Arab Emirates (UAE) remain unknown despite extensive COVID-19 vaccine coverage. The goal of this research is to establish the characteristics of COVID-19 breakthrough infections in the UAE's vaccinated population. Methods Between February and March 2022, we conducted a descriptive cross-sectional study in the UAE with 1533 participants to examine the characteristics of COVID-19 breakthrough infection among the vaccinated population. Results The vaccination coverage was 97.97%, and the COVID-19 breakthrough infection rate was 32.1%, requiring hospitalization in 7.7% of cases. The bulk of the 492 COVID-19 breakthrough infections reported was among young adults (67%), with the majority experiencing mild to moderate symptoms (70.7%) or remaining asymptomatic (21.5%). Conclusions COVID-19 breakthrough infection were reported in younger age, male sex, non-healthcare professions, vaccination with inactivated whole virus vaccine (Sinopharm), and not receiving a booster dose. Information on breakthrough infection in the UAE might influence public health decisions and motivate measures such as providing additional booster doses of the vaccines to the people.